Direct coupling of inert C–H bonds in NHC organocatalysis - Wang, Hongling (2024)
Direct coupling of inert C–H bonds by N-heterocyclic carbenes (NHCs) represents a fascinating area of research in organocatalysis. Recently, several notable studies have disclosed the potential of NHCs to directly functionalize latent C–H bonds of diverse simple molecules (e.g., ethers, amines, and arenes). These methodologies oﬀer straightforward and eﬃcient routes for C–C bond-forming transformations by diminishing the need for prefunctionalization manipulations of inert C–H bonds, allowing for the syn- thesis of a broad range of high value-added functional ketone molecules. Consequently, this highlight aims to present the latest advancements in NHC organocatalysis, speciﬁcally focusing on direct coupling functionalization of inert C–H bonds involving the electron or proton transfer process (ET/PT pathways) and hydrogen atom transfer pathway (HAT pathway).